(untitled) (Medico Legal Update, 2020)
The Indian Constitution guarantees equal right of justice, life and liberty to all Indian citizens. Every person has freedom of expression (unlawful act committed upon him/her) and it remains when the person died by any mean. Identification of an individual is primary element to investigate both civil and criminal cases. With the time, complexity of crime advance and forensic experts’ role become very crucial in investigation of crime. Crime investigation become very difficult and crucial when investigation agency find unknown mutilated body, bundle of bones or parts of bone. Without identification of dead person, investigation of crime become directionless. Key factor for identification are age, sex and stature. Many factors should be taken in to consideration to fix stature with help of bone. Many researchers had been clearly proved that long bone can be uses to estimate stature and it depend on race, ethnic and region. Very less work had been done to formulate regression formula from tibia in state of Gujarat. This study aims at formulate a regression formula to estimate stature from percutaneous length of tibia (PCTL) for native of Gujarat. This study was carried out in Department of Forensic Medicine, C.U. Shah Medical College, Surendranagar, Gujarat. Total 800 (400 male & 400 Female) undergraduate MBBS student between 18 to 25 years of age were participated in study. Their stature and percutaneous length of tibia were estimated with standard method and manner. Results are analysed and studied. Results show that there is highly significant in mean length of tibia and stature in both male and female participants (P<0.05). Stature and percutaneous length of tibia has positive correlation and regression formula is obtained to estimate stature from tibial length for natives of Gujarat.